Electronic Health Records Prospects in Egypt: A Demand-Side Perspective - Mona Farid Badran (International Telecommunications Society (ITS), 2017)
The present study sheds light on the expected factors that would impact the Electronic Health Records (EHR) service in Egypt from the demand-side perspective, i.e. the health care consumer. This empirical study is motivated by the widespread use of EHR as a method of promoting health services globally, where it is considered as an efficiency enhancing, cost effective technology. Moreover, the healthcare sector in Egypt is gaining momentum, especially that the comprehensive healthcare and social insurance law are expected to be discussed in the Egyptian Parliament in the near future. The underlying theoretical framework of this study implicates the Unified Theory of Acceptance and Use of Technology in Consumer Context (UTAUT2). It also applies an integrated framework from multifaceted perceptions to explain the expected adoption decision or behavior of the Egyptian consumer of EHR. The study relies on primary data, a survey of 559 respondents. Responses were collected by a telephone-based nationwide survey of respondents who completed college education or above. Their opinions were collected towards the EHR and the best way to apply this system in Egypt. The sample covered urban governorates, Lower Egypt and Upper Egypt, and it was collected in December 2015. Logistic regression results reveal that statistically significant constructs include the following: whether or not EHR is useful, willingness to pay for it, the gender perspective, the person in charge for uploading results, expected difficulties in using EHR, and the interaction term between gender and internet usage. Finally, more insight and recommendations are provided to policy makers.
Keywords: I10; I15; I18; L96; 330; Healthcare sector; e-health; UTAUT2; Egypt; Logistic regression